2002
DOI: 10.1093/jn/132.6.1235
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal and Milk Trans Octadecenoic Acid and Conjugated Linoleic Acid (CLA) Isomers Indicate that Postabsorptive Synthesis Is the Predominant Source of cis-9-Containing CLA in Lactating Dairy Cows

Abstract: Duodenal and milk samples obtained from lactating cows in a previous study were analyzed to compare the content and isomer distribution of conjugated linoleic acids (CLA) and trans-18:1 fatty acids (tFA). Four diets containing either low [25 g/100 g dry matter (DM)] or high (60 g/100 g DM) forage were fed with or without 2% added buffer to four multiparous Holstein dairy cows in a 2 x 2 factorial, 4 x 4 Latin square design with 3-wk experimental periods. Duodenal flows of CLA were low (1.02-1.84 g/d), compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
204
5
30

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(277 citation statements)
references
References 40 publications
38
204
5
30
Order By: Relevance
“…The linear increase in trans C18:1 concentration indicates that low ruminal pH favours trans C18:1 accumulation. Low ruminal pH, caused by a high-concentrate diet, increased the accumulation of trans C18:1 in other studies (Karlscheur et al, 1997;Piperova et al, 2002;Loor et al, 2004b). Although this study and others (Karlscheur et al, 1997;Piperova et al, 2002;Loor et al, 2004b) clearly show that low rumen pH promotes trans C18:1 accumulation, the mechanism is still unknown.…”
Section: Discussionsupporting
confidence: 38%
See 3 more Smart Citations
“…The linear increase in trans C18:1 concentration indicates that low ruminal pH favours trans C18:1 accumulation. Low ruminal pH, caused by a high-concentrate diet, increased the accumulation of trans C18:1 in other studies (Karlscheur et al, 1997;Piperova et al, 2002;Loor et al, 2004b). Although this study and others (Karlscheur et al, 1997;Piperova et al, 2002;Loor et al, 2004b) clearly show that low rumen pH promotes trans C18:1 accumulation, the mechanism is still unknown.…”
Section: Discussionsupporting
confidence: 38%
“…Low ruminal pH, caused by a high-concentrate diet, increased the accumulation of trans C18:1 in other studies (Karlscheur et al, 1997;Piperova et al, 2002;Loor et al, 2004b). Although this study and others (Karlscheur et al, 1997;Piperova et al, 2002;Loor et al, 2004b) clearly show that low rumen pH promotes trans C18:1 accumulation, the mechanism is still unknown. The accumulation of trans C18:1 under low rumen pH conditions may be caused by altering the rumen ecosystem and/or inhibiting the reductase activity of ruminal microorganisms, causing the accumulation of trans C18:1.…”
Section: Discussionsupporting
confidence: 38%
See 2 more Smart Citations
“…In our experiment, with diet C, the trans-13 1 14 18:1 proportion was 66% and 55% of that of trans-10 1 11 18:1 in plasma and milk, respectively, and proportions of trans-12 18:1, trans-15 18:1, and trans-16 18:1 were all around 10% of the total trans-18:1 in plasma and milk. Trans-12 18:1, trans-15 18:1, and trans-16 18:1 have already been suggested to be produced during cis-9, cis-12 18:2 BH (Loor et al, 2002), in addition to their production during cis-9 18:1 (Mosley et al, 2002) and cis-9, cis-12, cis-15 18:3 BH, and Piperova et al (2002) published a distribution of trans-18:1 isomers close to ours in the milk from cows fed a diet without added fat, and where cis-9, cis-12, cis-15 18:3 represented 10.8% of the total dietary FA. On the contrary, Loor et al (2005) found, with a diet without added fat but where cis-9, cis-12, cis-15 18:3 represented 25.8% of the total dietary FA, that trans-13 1 14 18:1 proportion was only 24% of that of trans-10 1 11 18:1 in milk, but 61% in plasma.…”
Section: Conjugated Linoleic and Linolenic Acids In The Milk Of Cows mentioning
confidence: 97%